Research on ultrasonic vibration assisted ploughing-extrusion process in forming μ-scale micro grooves. Issue 1 (1st December 2022) - Zhang, H D; Deng, L; Wang, X Y
Abstract : The surface micro groove structure on metallic components has received extensive attention for its role in improving the heat transfer coefficient. Limited by the size effect, it is difficult to manufacture μ-scale micro groove structure with large depth-to-width ratio through conventional extrusion or rolling processes. A novel UV assisted ploughing-extrusion process was proposed to manufacture μ-scale micro grooves. A series of UV assisted compression tests were conducted to study the acoustic deformation behavior of α-Ti, and a modified Ludwik model were established., The influence of deformation parameters was investigated, and the optimized deformation parameters are the leading angle is 60°, the extruded angle is 40°, and the ultrasonic amplitude is 10.30 μm. The results indicate that the novel ultrasonic vibration assisted ploughing-extrusion is able to continuously form large-sized micro-grooves parts with high quality.